2014
DOI: 10.1177/0300060513516944
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neutrophil lymphocyte ratio and blood glucose regulation in patients with type 2 diabetes mellitus

Abstract: There may be a significant relationship between NLR and blood glucose regulation. The authors propose that increased NLR may be associated with elevated HbA1c in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
74
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 29 publications
13
74
5
2
Order By: Relevance
“…Also, a similar association between NLR and metabolic disorders was recently reported by Buyukkaya et al [36], showing a positive association between serum glucose and NLR elevation, although HbA 1c values were not assessed in these patients. However, in contrast to our present data, Sefil et al [37] found a positive association between NLR and glycosylated haemoglobin levels, albeit in a small population of diabetics with poor glycaemic control. Moreover, a previous study had reported no relationship between neutrophil activation in diabetics and HbA 1c [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, a similar association between NLR and metabolic disorders was recently reported by Buyukkaya et al [36], showing a positive association between serum glucose and NLR elevation, although HbA 1c values were not assessed in these patients. However, in contrast to our present data, Sefil et al [37] found a positive association between NLR and glycosylated haemoglobin levels, albeit in a small population of diabetics with poor glycaemic control. Moreover, a previous study had reported no relationship between neutrophil activation in diabetics and HbA 1c [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Increased retinal neutrophil count damages retinal vascular endothelial cells and blood-retinal barrier through a Fas-Fas ligand-dependent pathway (Harris, Skalak, and Hatchell, 1994;Joussen et al, 2003;McLeod, Lefer, Merges, and Lutty, 1995). Recent reports confirmed that NLR is increased in T2DM and DR (Sefil et al, 2014;Shiny et al, 2014;Woo et al, 2011). In addition, elevated NLR was independently related with the severity of DR (Woo et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, NLR predicts presence, severity and extent of coronary artery disease, myocardial infarction in high risk patients for coronary artery disease, and peripheral arterial disease prognostication (Arbel et al, 2012;Bhat et al, 2013;Duffy et al, 2006;Horne et al, 2005;Nunez et al, 2008). More recently, some reports revealed that NLR is associated with glycated hemoglobin, different grades of glucose intolerance and insulin resistance, and the severity of DR (Sefil et al, 2014;Shiny et al, 2014;Woo, Ahn, Ahn, Park, and Lee, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Türkiye'de beta-talasemi taşıyıcılığının Çukurova, Hatay, İçel ve Antalya'yı içeren yüksek riskli bölgelerde popülasyon ortalamasının üzerine çıkmaktadır [1,3,4,16]. Bizim çalışmamızda evlilik öncesi taraması yapılan bireylerde beta-talasemi taşıyıcılığı %4.91 ile Türk Hemoglobinopati Konseyi tarafından yapılan çalışmadaki 16 şehrin ortalamasından yüksek tespit edilmiştir [18].…”
Section: Discussionunclassified